Impacts of climate change on freshwater ostracods (Crustacea, Ostracoda). - Conceição, Eliezer de Oliveira da (2021)
Species are exposed to natural climate change throughout their evolutionary history. However, anomalous global warming and resulting variations in rainfall patterns affect survival, alter the distribution of organisms and the network of species interactions. The aim of this thesis was to find larger-scale (basin and biome level) patterns for the possible effects of climate change on the distribution of South American freshwater ostracods through ensemble analysis of several species-distribution modelling algorithms. Here, climate change was based on two assumptions of increasing carbon emissions, the moderate-optimistic (RCP 4.5) and pessimistic (RCP 8.5) scenarios of four climate models (AOGCMs), from 2050 and 2080. In the first approach, projections of changes in ostracod species richness and composition were presented, and conservation status of 61 species from 13 river basins in the Southern Cone. In the second approach, the geographical pattern of a symbiotic interspecific interaction of commensalism type was evaluated through the climatic suitability of Elpidium (Ostracoda) and tank bromeliads of the Atlantic Forest, and the availability of habitat for Elpidium (presence of tank bromeliads) in the future. For both approaches, climate change directly influenced the decrease in future distribution areas of ostracods. The results of the first approach showed a decrease in ostracod richness in the Southern Cone basins of South America, and different species compositions in 2050 and 2080, in both the moderate-optimistic and pessimistic scenarios. The decrease in the ranges of ostracods will change the conservation status of several species to “potentially threatened”. Elpidium ranges will be more limited in the future, and there will be less habitat availability, i.e. fewer tank bromeliad species for interaction. In general, precipitation and temperature regimes are synchronized with phenological life-history events of the species, which determine the direction of dispersal to the environmental set of optimal survival conditions in the future. Our results contribute to the inclusion of ostracods (and other invertebrates) in conservation plans for their habitats on larger geographical scales.